Preparation method of patterned ceramic nanofiber-based gel electrolyte

By preparing an ordered patterned ceramic nanofiber-based gel electrolyte on the patterned conductive template, the problem of insufficient mechanical strength and toughness of the gel electrolyte is solved, and uniform conduction of lithium ions and dendrite inhibition is achieved, which is suitable for flexible lithium batteries.

CN119553501AActive Publication Date: 2025-03-04SHANGHAI SECOND POLYTECHNIC UNIVERSITY

Patent Information

Application Number
CN202411728730.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-04
Estimated Expiration
2044-11-28

AI Technical Summary

Technical Problem

The mechanical strength and toughness of existing gel electrolytes hinder the ability of lithium ion deposition and inhibit dendrites' growth. At the same time, the agglomeration and uneven distribution of ceramic nanofibers affect the performance of the electrolyte.

Method used

Using the preparation method of patterned ceramic nanofiber-based gel electrolyte, ceramic nanofiber membranes are prepared on patterned conductive templates through electrospinning technology, and polymer monomers and lithium salts are polymerized in situ on them to form an ordered ceramic nanofiber-based gel electrolyte.

Benefits of technology

The mechanical stability and conductivity of gel electrolytes are improved, the flux distribution of lithium ions is optimized, the growth of lithium dendrites is inhibited, and good electrochemical performance and mechanical flexibility are shown in flexible lithium batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119553501A_ABST
    Figure CN119553501A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of energy storage system device material preparation, and particularly relates to a preparation method of a patterned ceramic nanofiber-based gel electrolyte. A ceramic precursor salt is dissolved in a spinning solution, and a patterned conductive template is used as a receiver to obtain patterned precursor fibers; carrying out high-temperature roasting on the patterned precursor fiber to obtain a patterned ceramic nanofiber membrane; dropwise adding the gel precursor liquid onto a patterned ceramic nanofiber membrane, and waiting for polymerization to obtain a patterned ceramic nanofiber-based gel electrolyte; the surface of the ceramic nanofiber provides a rapid conduction channel for lithium ions, and the patterned structure effectively prevents irregular fibers from crossing to generate nodes, so that the ionic conductivity is further improved. The patterned ceramic nanofiber not only can optimize the structure of the polymer electrolyte and improve the mechanical stability of the polymer electrolyte, but also can uniformize the flux distribution of lithium ions and is beneficial to inhibiting the growth of lithium dendrites.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of energy storage system device material preparation, and specifically relates to a method for preparing a patterned ceramic nanofiber-based gel electrolyte. Background Art

[0002] Lithium metal has an extremely high theoretical specific capacity (3860mAh / g) and an extremely low electrode potential (-3.04V vs. standard hydrogen electrode), which gives lithium metal batteries a significant advantage in energy density and is expected to meet the urgent needs of electric vehicles, portable electronic devices, etc. for long battery life. Side reactions between lithium metal and traditional electrolytes can lead to continuous consumption of electrolytes and instability of the solid electrolyte interface (SEI) film. Unstable SEI films will continue to rupture and reconstruct, further exacerbating the occurrence of side reactions and affecting battery performance. In order to solve these problems, researchers have conducted in-depth research from multiple aspects. Including the development of new electrolyte systems, among many electrolyte materials, gel electrolytes (GPEs) have received increasing attention because they have both the high ionic conductivity of liquid electrolytes and the good mechanical properties of solid electrolytes.

[0003] Despite great progress in gel electrolytes, most current GPEs still suffer from low strength and toughness, which hinders their application in regulating Li + The ability to deposit and inhibit dendrite growth. Based on this problem, inorganic ceramic nanofillers have become an effective strategy to improve the mechanical strength and electrochemical properties of GPEs. However, due to the huge gap in surface energy between inorganic ceramics and organic polymers, high-concentration ceramics are very likely to agglomerate under traditional fillers, which seriously affects the overall performance of the electrolyte. In addition, at low ceramic concentrations, since the ceramic nanoparticles are dispersed from each other, a continuous ion transmission path cannot be formed, which also seriously affects the ion conductivity of the electrolyte. The preparation of pure ceramic nanofibers by electrospinning has become an effective method to solve the agglomeration and uneven distribution of ceramics. However, due to the instability of the charged liquid jet, traditional electrospinning usually produces irregular electrospinning membranes, and the nodes generated by the intersection of irregular nanofibers hinder the uniform conduction of lithium ions in the electrolyte, seriously affecting the performance of the electrolyte.

[0004] Therefore, it is of great significance to develop a new preparation method for patterned ceramic nanofiber-based gel electrolytes. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a method for preparing a patterned ceramic nanofiber-based gel electrolyte in view of the deficiencies in the prior art. The patterned ceramic nanofibers prepared by the present invention provide a channel for rapid conduction of lithium ions, and the orderly arrangement avoids the nodes generated by the intersection of irregular nanofibers, so that lithium ions can be conducted in the electrolyte without hindrance. The patterned ceramic nanofibers can optimize the structure of the polymer electrolyte, improve its mechanical stability, and help inhibit the growth of lithium dendrites. The material can be applied to flexible solid-state lithium batteries, and has both mechanical flexibility and good electrochemical properties.

[0006] In order to solve the above technical problems, the present invention discloses a method for preparing a patterned ceramic nanofiber-based gel electrolyte, the specific steps of which are:

[0007] S1. adding a ceramic precursor salt and a spinning aid to an organic solvent and mixing them uniformly to obtain a spinning solution;

[0008] S2. electrospinning the spinning solution, using a patterned conductive template as a receiver to obtain a patterned precursor fiber, and then calcining the patterned precursor fiber at a high temperature to obtain a patterned ceramic nanofiber membrane;

[0009] S3. Adding the polymer monomer and the lithium salt to the solvent and mixing them evenly to obtain a gel precursor liquid;

[0010] S4. Add the gel precursor liquid dropwise onto the patterned ceramic nanofiber membrane, and obtain a patterned ceramic nanofiber-based gel electrolyte after in-situ polymerization.

[0011] In S1, the molar ratio of the ceramic precursor salt to the spinning aid is (4-6):1; the mass ratio of the spinning aid to the organic solvent is 6-9%;

[0012] Preferably, the mass ratio of the spinning aid to the organic solvent is 6.5%.

[0013] In S1, the ceramic precursor salt is any one or a combination of lithium source, lanthanum source, zirconium source, titanium source and aluminum source; the spinning aid is any one or a combination of polyvinyl pyrrolidone, polyethylene oxide and polyvinyl alcohol; the organic solvent is any one or a combination of ethanol, pyridine and isopropanol.

[0014] Preferably, in S1, the ceramic precursor salt is one or a mixture of lithium source, lanthanum source, zirconium source and aluminum source; the spinning aid is polyvinyl pyrrolidone; and the organic solvent is ethanol;

[0015] More preferably, in S1, the ceramic precursor salt is lithium hydroxide, lanthanum nitrate hexahydrate, aluminum nitrate nonahydrate and zirconium acetate; the organic solvent is an aqueous solution of anhydrous ethanol, wherein the mass ratio is anhydrous ethanol: water = 1:1.

[0016] In S2, during the electrospinning process, the humidity environment is 20-35%, and the temperature environment is 30-35° C.; the electrospinning parameters are that the drum speed is 100-200 rpm, and the spinning solution injection speed is 0.5-2 ml / h; the patterned conductive template includes a grid shape, a honeycomb shape, and a circular hole shape;

[0017] Preferably, in S2, during the electrospinning process, the humidity environment is 40% and the temperature environment is 30°C; the electrospinning parameters are a drum speed of 100 rpm and a spinning solution injection speed of 0.8 ml / h; and the patterned conductive template is a grid-shaped 80-mesh stainless steel.

[0018] In S2, the high temperature calcination temperature is 700-1000°C and the temperature is kept for 1-2 hours;

[0019] Preferably, in S2, the high temperature calcination temperature is 850° C. and the temperature is kept for 2 hours.

[0020] In S3, the molar ratio of the polymer monomer to the solvent is (0.5-1.5):1; the concentration of the lithium salt in the gel precursor liquid is 0.5-2M;

[0021] Preferably, in S3, the molar ratio of the polymer monomer to the solvent is 1:1; and the concentration of the lithium salt in the gel precursor liquid is 2M.

[0022] In S3, the polymer monomer is any one of 1,3-dioxolane, 2-vinyl-2-ethyl-1,3-dioxolane, 4-methyl-1,3-dioxolane, 2,2-dimethyl-1,3-dioxolane, and 2-methyl-1,3-dioxolane, or a combination thereof; the solvent is any one of ethylene glycol dimethyl ether, dimethyl carbonate, vinylene carbonate, propylene carbonate, and ethylene carbonate, or a combination thereof; the lithium salt is any one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium trifluoromethanesulfonate, lithium bis(trifluoromethylsulfonyl)imide, and lithium difluoroborate, or a combination thereof;

[0023] Preferably, in S3, the polymer monomer is 1,3-dioxolane; the solvent is ethylene glycol dimethyl ether; and the lithium salt is lithium hexafluorophosphate and lithium bis(trifluoromethylsulfonyl)imide.

[0024] In S4, the reaction temperature of the in-situ polymerization is 10 to 60° C., and the reaction time is 0.5 to 48 h;

[0025] Preferably, in S4, the reaction temperature of the in-situ polymerization is 30° C. and the reaction time is 48 h.

[0026] Specifically, in some embodiments of the present invention, a patterned ceramic nanofiber-based gel electrolyte is prepared by the above-mentioned preparation method, and a ceramic nanofiber gel electrolyte battery is prepared.

[0027] Specifically, in some embodiments of the present invention, the electrochemical properties of the prepared ceramic nanofiber gel electrolyte battery are characterized, and through impedance testing, cycle testing and microscopic images of the lithium metal surface after the battery is cycled for 500 hours, it is proved that the patterned ceramic nanofiber-based gel electrolyte prepared by the present invention has good performance in lithium batteries, verifying the application prospects of patterned ceramic nanofiber-based gel electrolytes in the field of flexible lithium battery preparation.

[0028] Beneficial effects:

[0029] (1) The presence of ceramic nanofibers greatly improves the chemical stability of the gel electrolyte;

[0030] (2) The surface of ceramic nanofibers can provide a channel for rapid conduction of lithium ions. Compared with randomly dispersed nanofibers, ordered nanofibers avoid the nodes generated by the intersection of irregular nanofibers, allowing lithium ions to conduct unimpeded in the electrolyte, further improving the conductivity of the gel electrolyte.

[0031] (3) Patterned ceramic nanofibers can optimize the structure of polymer electrolytes and uniformly coat Li + The flux distribution helps to inhibit the growth of lithium dendrites;

[0032] (4) The obtained patterned ceramic nanofiber-based gel electrolyte can be used in lithium batteries and has good electrochemical properties and mechanical flexibility. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments, and the above and / or other advantages of the present invention will become more clear.

[0034] Figure 1 This is a SEM image of the patterned ceramic nanofiber membrane prepared in Example 1;

[0035] Figure 2 This is a SEM image of the patterned ceramic nanofiber membrane prepared in Example 2;

[0036] Figure 3 This is a SEM image of the patterned ceramic nanofiber membrane prepared in Comparative Example 1;

[0037] Figure 4 XRD diagram of the patterned ceramic nanofiber membrane prepared in Examples 1 and 2;

[0038] Figure 5 The impedance spectrum of the patterned ceramic nanofiber gel electrolyte battery prepared in Example 2;

[0039] Figure 6 The cycle test diagram of the ceramic nanofiber gel electrolyte battery prepared in Example 2 and Comparative Example 1;

[0040] Figure 7 This is a SEM image of the lithium metal surface of the patterned ceramic nanofiber-based gel electrolyte lithium metal battery prepared in Example 2 after cycling for 500 hours;

[0041] Figure 8 SEM image of the lithium metal surface of the non-patterned ceramic nanofiber-based gel electrolyte lithium metal battery prepared in Comparative Example 1 after cycling for 500 hours. DETAILED DESCRIPTION

[0042] The experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.

[0043] Embodiment 1:

[0044] A method for preparing a patterned ceramic nanofiber-based gel electrolyte. The specific steps are as follows:

[0045] (1) adding 6.5 wt % polyvinyl pyrrolidone to a mixed solution of deionized water and anhydrous ethanol (mass ratio of deionized water to anhydrous ethanol = 1:1), stirring evenly, then adding 0.0118 mol lithium hydroxide, 0.0048 mol lanthanum nitrate hexahydrate, 0.0003 mol aluminum nitrate nonahydrate, and 0.0058 mol zirconium acetate, and stirring the solution evenly to obtain an electrospinning solution;

[0046] (2) Electrospinning was performed under the conditions of an ambient temperature of 30°C and a humidity of 40%, using an 80-mesh stainless steel grid as a collector, a drum speed of 500 rpm, an injection speed of 0.8 ml / h, and an electrostatic voltage of 10 KV. Under these conditions, the electrospinning solution was prepared into a patterned precursor fiber. Subsequently, the patterned ceramic nanofiber membrane was obtained by calcining in a muffle furnace at 850°C for 2 h;

[0047] (3) Lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) and lithium hexafluorophosphate (LiPF6) were dried in a vacuum drying oven for later use, and appropriate amounts of LiTFSI and LiPF6 were dissolved in a mixed solution of 1,3-dioxolane (DOL) and ethylene glycol dimethyl ether (DME) to obtain a gel precursor solution, wherein the molar ratio of DOL to DME was 1:1, the amount of LiTFSI added was 1 M, and the amount of LiPF6 added was 1 M, and the mixture was stirred for 1 h;

[0048] (4) Add 50 μL of the gel electrolyte precursor liquid prepared in step (3) onto the patterned ceramic nanofiber membrane prepared in step (2) to fully soak it, load a stainless steel symmetrical battery to measure its ionic conductivity, load a lithium symmetrical battery to measure the cycle performance, and gel for 48 hours at an ambient temperature of 30°C to obtain a gridded ceramic nanofiber gel electrolyte battery.

[0049] Embodiment 2:

[0050] A method for preparing a patterned ceramic nanofiber-based gel electrolyte. The specific steps are as follows:

[0051] (1) adding 6.5 wt % polyvinyl pyrrolidone to a mixed solution of deionized water and anhydrous ethanol (mass ratio of deionized water to anhydrous ethanol = 1:1), stirring evenly, then adding 0.0118 mol lithium hydroxide, 0.0048 mol lanthanum nitrate hexahydrate, 0.0003 mol aluminum nitrate nonahydrate, and 0.0058 mol zirconium acetate, and stirring the solution evenly to obtain an electrospinning solution;

[0052] (2) Electrospinning was performed under the conditions of an ambient temperature of 30°C and a humidity of 40%, using an 80-mesh stainless steel grid as a collector, a drum speed of 100 rpm, an injection speed of 0.8 ml / h, and an electrostatic voltage of 10 KV. Under these conditions, the electrospinning solution was prepared into a patterned precursor fiber. Subsequently, the patterned ceramic nanofiber membrane was obtained by calcining in a muffle furnace at 850°C for 2 h;

[0053] (3) Lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) and lithium hexafluorophosphate (LiPF6) were dried in a vacuum drying oven for later use, and appropriate amounts of LiTFSI and LiPF6 were dissolved in a mixed solution of 1,3-dioxolane (DOL) and ethylene glycol dimethyl ether (DME) to obtain a gel precursor solution, wherein the molar ratio of DOL to DME was 1:1, the amount of LiTFSI added was 1 M, and the amount of LiPF6 added was 1 M, and the mixture was stirred for 1 h;

[0054] (4) Add 50 μL of the gel electrolyte precursor liquid prepared in step (3) onto the patterned ceramic nanofiber membrane prepared in step (2) to fully soak it, load a stainless steel symmetrical battery to measure its ionic conductivity, load a lithium symmetrical battery to measure the cycle performance, and gel for 48 hours at an ambient temperature of 30°C to obtain a gridded ceramic nanofiber gel electrolyte battery.

[0055] Comparative Example 1:

[0056] A method for preparing a non-patterned ceramic nanofiber-based gel electrolyte. The specific steps are as follows:

[0057] (1) adding 6.5 wt % polyvinyl pyrrolidone to a mixed solution of deionized water and anhydrous ethanol (mass ratio of deionized water to anhydrous ethanol = 1:1), stirring evenly, then adding 0.0118 mol lithium hydroxide, 0.0048 mol lanthanum nitrate hexahydrate, 0.0003 mol aluminum nitrate nonahydrate, and 0.0058 mol zirconium acetate, and stirring the solution evenly to obtain an electrospinning solution;

[0058] (2) Electrospinning was performed under the conditions of an ambient temperature of 30°C and a humidity of 40%, with aluminum foil used as a collector for collection, a drum speed of 100 rpm, an injection speed of 0.8 ml / h, and an electrostatic voltage of 10 KV. Under these conditions, the electrospinning solution was prepared into a patterned nanofiber membrane. Subsequently, the non-patterned ceramic nanofiber membrane was obtained by calcining in a muffle furnace at 850°C for 2 h;

[0059] (3) Lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) and lithium hexafluorophosphate (LiPF6) were dried in a vacuum drying oven for later use, and appropriate amounts of LiTFSI and LiPF6 were dissolved in a mixed solution of 1,3-dioxolane (DOL) and ethylene glycol dimethyl ether (DME) to obtain a gel precursor solution, wherein the molar ratio of DOL to DME was 1:1, the amount of LiTFSI added was 1 M, and the amount of LiPF6 added was 1 M, and the mixture was stirred for 1 h;

[0060] (4) Add 50 μL of the gel electrolyte precursor liquid prepared in step (3) onto the non-patterned ceramic nanofiber membrane prepared in step (2) to fully soak it, load the battery, and gel for 48 hours at an ambient temperature of 30°C to obtain a non-grid ceramic nanofiber gel electrolyte battery.

[0061] Structural characterization of patterned ceramic nanofiber membranes:

[0062] The ceramic nanofiber membranes obtained in step (2) of Example 1, Example 2 and Comparative Example 1 were characterized by scanning electron microscopy (SEM). Figure 1This is a SEM image of the patterned ceramic nanofiber membrane prepared in Example 1. Figure 2 This is a SEM image of the patterned ceramic nanofiber membrane prepared in Example 2. Figure 3 The SEM image of the patterned ceramic nanofiber membrane prepared in Comparative Example 1 is Figure 1 to Figure 3 It can be seen that the comparative example 1 uses aluminum foil as a collector and cannot obtain a gridded ceramic nanofiber membrane. Compared with the embodiment 2, the roller speed in the spinning process of the embodiment 1 increases, which is not conducive to the formation of the grid. The weakening of the grid structure affects the Li + Uniformity of transport in the electrolyte.

[0063] The patterned ceramic nanofiber membrane obtained in step (2) of Examples 1 and 2 was characterized by an X-ray diffractometer. Figure 4 The XRD diagrams of the patterned ceramic nanofiber membranes prepared in Examples 1 and 2 show that the patterned ceramic nanofiber membranes prepared in the present invention conform to the crystalline phase of ceramics, proving that they are ceramics with fewer impurities.

[0064] Performance characterization of patterned ceramic nanofiber-based gel electrolyte batteries:

[0065] The impedance test of the gridded ceramic nanofiber gel electrolyte prepared in Example 2 was performed. The specific method was as follows: assembling SS / / GPEs / / SS batteries, using an electrochemical workstation to test the electrochemical impedance spectroscopy (EIS) in the frequency range of 1 MHz-0.1 Hz, and the ionic conductivity (σ) was calculated by formula 1: Where R is the resistance value of the bulk solid electrolyte, L is the thickness of the electrolyte membrane, and S is the effective contact area between the electrolyte and the stainless steel electrode; Figure 5 As its impedance spectrum, according to the formula, it can be calculated that the conductivity of the ceramic nanofiber gel electrolyte battery prepared in Example 2 reaches 10 -3 S / cm.

[0066] The ceramic nanofiber gel electrolyte battery prepared in Example 2 and Comparative Example 1 was subjected to a cycle test. The specific method was as follows: Li / / GPEs / / Li battery was assembled, and the Li symmetric battery was measured at 0.5 mA cm using an electrochemical workstation. -2 Cycling performance at a current density of 0.5 mAh cm -2 ; Figure 6 The battery cycle diagram of Example 2 and the comparative example for 1000 hours. It can be seen from the figure that the polarization voltage of Example 2 is still stable after 1000 hours of cycling, proving that the grid-based battery has a stable polarization voltage.

[0067] The lithium metal surface of the gridded ceramic nanofiber gel electrolyte battery prepared in Example 2 and Comparative Example 1 after cycling for 500 h was characterized using a scanning electron microscope (SEM). Figure 7 This is a SEM image of the lithium metal surface of the patterned ceramic nanofiber-based gel electrolyte lithium metal battery prepared in Example 2 after cycling for 500 hours. Figure 8 This is the SEM image of the lithium metal surface of the non-patterned ceramic nanofiber-based gel electrolyte lithium metal battery prepared in Comparative Example 1 after cycling for 500 hours. It can be seen from the figure that the lithium metal surface of the battery without gridding has more dendrite growth, while the one with gridding is relatively flat, proving that the grid has the function of regulating Li dendrites.

[0068] The present invention provides a method for preparing a patterned ceramic nanofiber-based gel electrolyte. There are many methods and ways to implement the technical solution. The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention. All components not specified in this embodiment can be implemented by existing technologies.

Claims

1. A method for preparing a patterned ceramic nanofiber-based gel electrolyte, characterized in that: The specific steps are: S1. adding a ceramic precursor salt and a spinning aid to an organic solvent and mixing them uniformly to obtain a spinning solution; S2. electrospinning the spinning solution, using a patterned conductive template as a receiver to obtain a patterned precursor fiber, and then calcining the patterned precursor fiber at a high temperature to obtain a patterned ceramic nanofiber membrane; S3. Adding the polymer monomer and the lithium salt to the solvent and mixing them evenly to obtain a gel precursor liquid; S4. Add the gel precursor liquid dropwise onto the patterned ceramic nanofiber membrane, and obtain a patterned ceramic nanofiber-based gel electrolyte after in-situ polymerization.

2. The preparation method according to claim 1, characterized in that: In S1, the molar ratio of the ceramic precursor salt to the spinning aid is (4-6):1; the mass ratio of the spinning aid to the organic solvent is 6-9%.

3. The preparation method according to claim 2, characterized in that: The ceramic precursor salt is any one or a combination of lithium source, lanthanum source, zirconium source, titanium source and aluminum source; the spinning aid is any one or a combination of polyvinyl pyrrolidone, polyethylene oxide and polyvinyl alcohol; the organic solvent is any one or a combination of ethanol, pyridine and isopropanol.

4. The preparation method according to claim 1, characterized in that: In S2, during the electrospinning process, the humidity environment is 20-35%, and the temperature environment is 30-35°C; the parameters of the electrospinning are a drum speed of 100-200 rpm and a spinning solution injection speed of 0.5-2 ml / h; the shapes of the patterned conductive template include grid, honeycomb and circular hole.

5. The preparation method according to claim 1, characterized in that: In S2, the high temperature calcination temperature is 700-1000°C and the temperature is kept for 1-2 hours.

6. The preparation method according to claim 1, characterized in that: In S3, the molar ratio of the polymer monomer to the solvent is (0.5-1.5):1; the concentration of the lithium salt in the gel precursor liquid is 0.5-2M.

7. The preparation method according to claim 6, characterized in that: The polymer monomer is any one of 1,3-dioxolane, 2-vinyl-2-ethyl-1,3-dioxolane, 4-methyl-1,3-dioxolane, 2,2-dimethyl-1,3-dioxolane, and 2-methyl-1,3-dioxolane, or a combination thereof; the solvent is any one of ethylene glycol dimethyl ether, dimethyl carbonate, vinylene carbonate, propylene carbonate, and ethylene carbonate, or a combination thereof; and the lithium salt is any one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium trifluoromethanesulfonate, lithium bis(trifluoromethylsulfonyl)imide, and lithium difluoroborate, or a combination thereof.

8. The preparation method according to claim 1, characterized in that: In S4, the reaction temperature of the in-situ polymerization is 10 to 60° C., and the reaction time is 0.5 to 48 hours.

9. The patterned ceramic nanofiber-based gel electrolyte prepared by the preparation method according to any one of claims 1 to 8.

10. Application of the patterned ceramic nanofiber-based gel electrolyte described in claim 9 in the field of flexible lithium battery preparation.

Citation Information

Patent Citations

  • Preparation method of nano-doped grid patterning gel polymer electrolyte

    CN104638294A

  • Preparation method of gradient fiber structure composite gel polymer electrolyte for lithium battery

    CN119009095A

  • Polymer electrolyte, lithium secondary battery using same, and method for manufacturing lithium secondary battery

    US20150318570A1

  • Secondary battery

    WO2018131894A1

Cited By

  • Two-dimensional honeycomb-shaped and three-dimensional spinous process-shaped double-coupled microstructure nanofiber membrane as well as preparation method and application thereof

    CN119956557A

  • Two-dimensional honeycomb and three-dimensional spine-shaped double-coupling microstructure nanofiber membrane, and preparation method and application thereof

    CN119956557B